Analisis Nilai-Nilai Edukatif untuk Siswa Sekolah Dasar pada Cerita Rakyat Bujang Kurap - Lailia Ulfa; Haryadi Haryadi (Journal of Elementary School (JOES), 2022)
This study aims to determine the educational values ​​of the folklore of the archipelago, especially the story of Bujang Kurap. This research is a qualitative research by applying descriptive method in the process. Based on the results of the descriptive analysis conducted on the Bujang Kurap folklore, there are educational values ​​that can be used as motivation for students to improve the moral values ​​and behavior of students today. The story of Bujang Kurap has educational values, such as: 1) Patience; 2) Respect between fellow human beings; 3) Keep every promise that has been made; 4) there will be reciprocity of what every human being does. Conclusion, the folklore of single ringworm has educational values that can be used as one of the suggestions that can improve children's morale. Keywords: Educational Value, Folklore, Bujang Kurap